Digital Students’ Satisfaction With and Intention to Use Online Teaching Modes, Role of Big Five Personality Traits - Mustafa, Sohaib; Qiao, Yu; Yan, Xin; Anwar, Aliya; Hao, Tengyue; Rana, Sehrish (Frontiers in Psychology, 2022)
During the covid-19 pandemic, online teaching modes were found vital to continue students learning process, but a sustainable implementation of online teaching models is an area of concern for policymakers. Psychiatrists are also eager to know students' behavior towards learning and modes of teaching during covid-19. We have drawn a model based on the big five personality traits to study the students' satisfaction with online teaching modes and their adoption intentions towards online teaching modes. We have collected data from 718 bachelor's and master's level students from 4 different universities. We have applied the SEM-ANN dual-stage approach to test personality traits influence and ranked them based on their normalized importance. The results revealed that Agreeableness, Conscientiousness, Neuroticism, and Openness positively influence students' satisfaction with online teaching models, but Extraversion negatively influence their satisfaction. Agreeableness, Extraversion, and Neuroticism positively impact, but Openness negatively influences. Conscientiousness does not affect adoption intention. Furthermore, Agreeableness is the most significant, and Conscientiousness is the least important factor for students to adopt online teaching modes. The study findings have useful perceptiveness for educational policymakers, academics and Psychiatrists.